Two-step communication for the interaction between automated vehicles and pedestrians. (October 2022) - Bindschädel, Janina; Krems, Ingo; Kiesel, Andrea
Highlights: Analysis of a two-step communication concepts for automated vehicles which provided implicit and explicit communication cues at two distances. Comparison of two-step and single-step communication concepts. Beneficial effect of single-step communication concepts on pedestrians' crossing behavior and safety feeling, no further improvements by two-step communication concepts. Analysis of fixation patterns in pedestrian interactions with automated vehicles. Consistent pattern of pedestrians' fixation behavior as a function of the automated vehicle's distance. Abstract: An important challenge of automated vehicles (AV) will be the cooperative interaction with surrounding road users such as pedestrians. One solution to compensate for the missing driver-pedestrian interaction might be explicit communication via external human machine interfaces (eHMIs). Additionally, implicit communication such as a vehicle pitch motion might support AVs when interacting with pedestrians. While previous work explored various explicit and implicit communication cues, these concepts communicated the intention of the AV at one single time point. Currently, empirical findings on two-step communication lack so far. In this study, we empirically test the effect of a two-step AV communication that uses an implicit cue at a long distance and subsequently provides an implicit or explicit cues at a short distance. We compared its efficiency to single-step communication concepts providing implicit or explicit cues at the shorter distance only. To explore whether the right communication cue is used at the right distance, we analyzed pedestrians' fixations while approaching an AV using an eye tracking device. We conducted a virtual reality study ( N  = 30) with AV communication concept that provided an active pitch motion or an eHMI and compared them with a two-step AV communication concept that provided an additional active pitch motion at a long distance when approaching the pedestrian. Furthermore, we recorded pedestrians' fixation behavior while the AV approached. Consistently to previous work, single-step AV communication showed a beneficial effect on crossing behavior. Pedestrians initiated their crossing earlier while approaching an AV with an active pitch motion or an eHMI compared to the baseline condition. While active pitch motion reduced subjective safety feeling, eHMI increased it. However, the two-step communication concept did not further improve pedestrians' crossing initiation times and their safety feeling. The pattern of fixation behavior differed as a function of AV distance. When the approaching AV was far away, pedestrians exclusively looked at the environment. During the approach, pedestrians gradually fixated the bumper and the hood and only then the windshield of the AV. Hence, it seems to be useful to present an AV intent communication at a certain distance from the pedestrian. These findings posit the importance of considering pedestrians' fixation behavior when developing communication concepts between AVs and pedestrians.